Psychological and pedagogical potential of life orientations of spouses with various dominant marital behavior //Potencial psicológico y pedagógico de las orientaciones de vida de los cónyuges con diversos comportamientos maritales dominantes - Latysheva, Marianna A.; Suleymanova, Zumrud Z.; Magomedova, Patimat N.; Kulikov, Sergey V. (Journal of the University of Zulia, 2020)
Abstract The article is devoted to the problem of transformation of family values, the emergence of new types of families in the context of modern marriage. The authors believe that in post-Soviet society in Russia, the axiological approach is the most heuristic in the study of marriage. The authors used a psychological analysis of the life-meaning orientations of spouses with a traditional type of marriage and spouses focused on voluntary childlessness. The results of the study showed that the specifics of life and life orientations of the husband and wife, their personal characteristics determine the attitudes and expectations of marital relations, the choice of the type of family. It was revealed that the life orientations of spouses who support voluntary childlessness are contradictory: men, when they are dissatisfied with their lives in the present and not confident in their abilities, focused on getting pleasure as the meaning of life here and now; and the wife, experiencing the riches of his life, demonstrating the confidence, commitment to the future, a higher meaning of life. Spouses from the traditional type of family are both happy with their lives. At the same time, husbands are characterized by an average level of meaningfulness of life, focus on the implementation of current tasks, and wives with a high sense of life are focused on the future, are confident in the possibility of building a life in accordance with their ideas about its meaning and life goals. Resumen El artículo está dedicado al problema de la transformación de los valores familiares, la aparición de nuevos tipos de familias en el contexto del matrimonio moderno. Los autores creen que en la sociedad postsoviética de Rusia, el enfoque axiológico es el más heurístico en el estudio del matrimonio. Los autores utilizaron un análisis psicológico de las orientaciones del significado de la vida de los cónyuges con un tipo de matrimonio tradicional y los cónyuges centrados en la falta voluntaria de hijos. Los resultados del estudio mostraron que las características específicas de la vida y las orientaciones de vida del esposo y la esposa, sus características personales, determinan las actitudes y expectativas de las relaciones matrimoniales, la elección del tipo de familia. Se reveló que las orientaciones de vida de los cónyuges que apoyan la ausencia voluntaria de hijos son contradictorias: los hombres, cuando están insatisfechos con su vida en el presente y no confían en sus capacidades, se centran en obtener el placer como sentido de la vida aquí y ahora; y la esposa, experimentando las riquezas de su vida, demostrando confianza, compromiso con el futuro, presenta un sentido superior de la vida. Los cónyuges del tipo de familia tradicional están felices con sus vidas. Al mismo tiempo, los esposos se caracterizan por un nivel promedio de significado de la vida, se enfocan en la implementación de las tareas actuales y las esposas con un alto sentido de la vida se enfocan en el futuro, confían en la posibilidad de construir una vida de acuerdo con sus ideas sobre su significado y objetivos de vida.